Intact β-Cryptoxanthin Prevention of Cigarette Smoke-Induced Inflammatory Lung Lesions Independent of Carotenoid Cleavage Enzymes and Mechanistic Understanding of Sirtuin 1 Activity - Chiaverelli, Rachel Anna. (2018)
Abstract: Cigarette smoke (CS) inhalation remains a major public health problem. Chronic inflammation induced by CS is known to be the underlying mechanism for many diseases. Inflammation from CS-exposure has been shown to lead to bronchitis and emphysema, which together, chronically, lead to irreversible damage and chronic obstructive pulmonary disease (COPD). COPD remains a leading cause of hospitalization and is expected to become the third most common cause of death by 2020. Currently, therapeutic interventions for COPD only help with the symptoms of the disease, but no cure exits. Therefore, the need for the discovery of dietary preventative agents is necessary. Several epidemiological studies, including the National Health and Nutrition Examination Survey (NHANES) and the Seven Cohorts Studies, have shown an increase in the plasma levels of carotenoids was associated with lower risk of chronic lung disease. Specifically, β-cryptoxanthin (BCX), a pro-vitamin A carotenoid abundantly found in butternut squash, pumpkin, citrus fruits, papaya, and sweet red peppers, was the only carotenoid for which intake was associated with a lower risk of lung disease, such as lung cancer, in current smokers. However, the protective effect of BCX against other lung diseases, such as emphysema as a result from CS-induced inflammation has not been investigated. Moreover, the biologically active effects of intact BCX, without the generation of vitamin A or apo-10'-carotenoids, via β-carotene-15,15'-oxygenase (BCO1) and β-carotene-9',10'-oxygenase (BCO2), respectively, has not been investigated. BCO1/BCO2 polymorphism has been associated with alterations in human and animal carotenoid level status, consequently impacting the generation of vitamin A and apo-carotenoids generated by BCO1/BCO2, which possess strong, well-known biological activities. However, whether the presence of BCO1/BCO2 polymorphisms in the human population has implications in carotenoid metabolism and function remains unclear. In this thesis work, we investigated whether BCX possesses anti-inflammatory biological activity to prevent CS-induced inflammation and lung lesion development and the potential mechanism(s) involved, and whether this biological activity is independent of, or dependent on, carotenoid cleavage enzymes, BCO1/BCO2. In the first part of this study, we examined the preventative effects of biologically active, intact BCX supplementation (20 mg/kg diet), against two weeks of CS-exposure in both wild type (WT) and BCO1/BCO2 double knock out (DKO, BCO1-/-/BCO2-/- which both BCO1 and BCO2 cleavage enzymes have been knocked out) mouse model, including males and females. We observed that BCX supplementation was able to significantly reduce CS-induced inflammation and emphysema in both DKO and WT mice in the same manner, as measured by inflammatory cell infiltration and the average distance between alveolated membranes (Lm) and hyperplastic bronchiolars, respectively, therefore no genotype effect was revealed. This response was associated with HPLC analysis of the liver, which demonstrated a significant accumulation of BCX in both mouse genotypes, with less accumulation in the WT mice. Moreover, as expected, WT mice showed a significant increase in retinol generation when fed BCX, whereas DKO did not show any change in retinol levels. Thus, indicating a protective effect of BCX due to the activities of intact BCX. Molecularly, the pathological findings of intact BCX biological activities were consistent with reduced the gene expression of inflammatory cytokines (IL6 and TNFα) and matrix metalloproteinases (MMP-2 and MMP-9), related to inflammation and inflammatory lung lesion development. No sex differences were observed. This part of the thesis provides the first in vivo evidence that intact BCX possesses its own anti-inflammatory activity, and has protective effects against CS-induced lung lesions, independent of the generation of vitamin A or apo-10'-carotenoids. In the second part of this thesis work, we aimed to examine the underlying mechanism by which inflammatory lung lesions develop in response to CS. Sirtuin 1 (SIRT1), a nicotinamide adenine dinucleotide (NAD+)-dependent deacetylase, known for its anti-inflammatory and anti-aging activity, has been introduced as a potential target of CS due to its sensitivity to redox status and inflammation. Moreover, decreased levels of SIRT1 protein have been found in patients suffering from COPD, however much controversy exists over the implications of SIRT1 protein levels versus its activity, therefore SIRT1 protein levels alone cannot be used to reflect its deacetylase activity. To address this question, we conducted a CS-exposure study using both male and female mice which have been genetically modified so that they do not have whole body SIRT1 enzymatic activity (Sirt1y/y), or have partial SIRT1 enzymatic activity (Sirt1+/y), compared to wild type (WT) mice with fully functioning SIRT1 enzymatic activity (Sirt1+/+). Following CS-exposure for six weeks, Sirt1+/+ and Sirt1+/y mice had a significant inflammation response compared to Sirt1+/+ mice not exposed to CS. To our surprise, Sirt1y/y mice exposed to CS produced a weak inflammatory response, but did have an exacerbation of emphysema, compared to Sirt1+/+ and Sirt1+/y mice. We investigated this novel finding molecularly and discovered a significant decrease in transcription factors related to cell cycle progression and a significant increase in markers of cellular senescence in the lungs of both Sirt1+/y and Sirt1y/y mice. Specifically, we discovered a CS-induced decrease in transcription factor, p53, which is related to the regulation of cell cycle progression. Consistent with these findings, we revealed a decrease in cell cycle progression (cyclin-dependent kinase 1, CDK1) and an increase in biomarkers for cell arrest/cellular senescence (p21 and p16), which is likely the underlying mechanism for emphysema development, independent of inflammation. We did not observe sex differences. The second part of this thesis presents evidence that the whole-body loss of SIRT1 enzymatic activity results in the exacerbation CS-induced emphysema with much less of an inflammatory response, as compared with WT mice. This study lays the groundwork for further investigation of SIRT1 enzymatic activity's role in CS-induced cell arrest and senescence as the underlying mechanism for emphysema development. Taken together, using two genetically modified mouse models, this thesis work demonstrates that, first, intact BCX, independent of carotenoid cleavage enzymes is a strong anti-inflammatory agent against CS-induced inflammation and lung lesions without sex differences; and, secondly, SIRT1 enzymatic activity plays a major role in the underlying mechanism of emphysema induction due to cell arrest and senescence, without sex differences.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Biochemical and Molecular Nutrition.; Advisor: Xiang-Dong Wang.; Committee: Dayong Wu, Irfan Rahman, and Virendar Kaushik.; Keywords: Biochemistry, Nutrition, and Molecular biology.